Perlindungan Hukum Bagi Pembeli Dalam Sengketa Jual Beli Online - Aditya Ayu Hakiki , Asri Wijayanti, Rizania Kharismasari (Universitas Muhammadiyah Surabaya, 2017)
In community disputes often occur online purchase adverse buyers. The purpose of this study was to determine the forms of legal protection and remedies for aggrieved buyers in selling and buying online dispute. This research is normative juridical approach to legislation. Results of the first study is a form of legal protection for the buyer in a dispute over online trading that is the rule of law on the rights and obligations of the seller and the buyer (Article 1473-1519 BW), proof of electronic transactions (Article 5 of Law No. 11 of 2008), right to sue tort (Article 1365 BW) if the aggrieved buyer can file a lawsuit based on their default. Results of the second study are legal remedies which can be done by consumers were harmed in selling and buying online dispute consists of litigation (PN, PT, MA Article 48 of Law No. 8 of 1999 jo. Article 38 of Law No. 11 of 2008) and non-litigation through mediation, conciliation or arbitration (Article 39 of Law No. 11 of 2008). The resulting recommendations are needed socialization of legal protection under the Act ITE